2002
DOI: 10.1016/s0738-3991(02)00011-3
|View full text |Cite
|
Sign up to set email alerts
|

Does writing a list help cancer patients ask relevant questions?

Abstract: We examined the use of written lists to give patients an opportunity to have their questions answered. Patients undergoing radical radiotherapy for cancer were given a sheet of paper with the simple prompt to write questions and give to the hospital doctor at their appointment 3 weeks later. At 3 months, patients were asked about their use and opinions of the written list. About half of the 478 patients attended with a written list. Fewer patients living in deprived areas used the list compared to more affluen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 9 publications
1
16
1
Order By: Relevance
“…One possible explanation for the different result between this and our previous study is that in the previous study all patients were encouraged to write a list of questions to ask their oncolo-gist one week after the intervention 14. Other researchers have shown the possible beneficial effect of prompt sheets and written lists on anxiety 15.…”
Section: Discussioncontrasting
confidence: 56%
“…One possible explanation for the different result between this and our previous study is that in the previous study all patients were encouraged to write a list of questions to ask their oncolo-gist one week after the intervention 14. Other researchers have shown the possible beneficial effect of prompt sheets and written lists on anxiety 15.…”
Section: Discussioncontrasting
confidence: 56%
“…This finding suggests that counselees need to be motivated to write down their own questions, and this advice should be more accessible and might best be placed at the homepage of future websites that include a QPS. Only half of the counselees wrote down questions, which is comparable to the findings of Jones et al with a blank QPS for cancer patients undergoing radiotherapy [54]. A study of oncology outpatients found higher QPS use, three fourths of all patients [30], and the advice about why to use the QPS might explain this higher uptake.…”
Section: Discussionsupporting
confidence: 68%
“…• To remind patient to make notes of questions to ask or instructions to follow 41 Contain contact details for health care services • To ensure reader can contact ward or department in case of questions or emergency 17 …”
mentioning
confidence: 99%